ABC transporter transcription regulation by Staphylococcus aureus SAOUHSC01313-01314 Two Component System - Diaz, Alejandra Raquel (2017)
Staphylococcus aureus, a G+ bacterium, is a frequent component of human microbiota that can turn into a dangerous pathogen. The pathogenicity of this bacterium is caused by expression of a myriad of virulence factors. Since two component systems (TCSs) are the principal mechanism involved in stress response, we studied two contiguous genes located in strain NCTC 8325, SAOUHSC01313-01314, coding for a membrane-histidine kinase (HK) and a response regulator, respectively. These genes showed homology with Bacillus subtilis DesKR, which regulates transcription of its sole desaturase in response to changes in membrane fluidity. The TCSsa is located downstream of genes encoding a putative ABC transporter (SAOUHSC01311-SAOUHSC01312) that carries in its promoter a box very similar to the regulatory region of des. This TCS/ABC link resembles the prototype detoxification module found in Firmicutes. In order to study the transcriptional activation of the ABC transporter by the TCS we constructed a transcriptional fusion of SAOUHSC01311 promoter to lacZ, in plasmid pTCVlac. This plasmid, pARD22, was transformed in wild type strains RN4220 and SH1000, and the derivatives ΔSAOUHSC01313-01314, strains ARD10 and ARD11, respectively. β-gal assays of strains carrying pARD22 were conducted at different temperatures and media composition. We found that the TCSsa regulates the transcription of the genes encoding the ABC transporter in a temperature dependent fashion. However, in contrast to the des gene, transcription was induced at 37°C rather than at low temperature. We also found that expression of the ABC transporter occurs in stationary phase, and requires minerals and sugars in the culture medium. These results show that, despite the similarity between DesK and SAOUHSC01313, the HKsa responds to different stimuli, and shed light on the possible role of this HK in the membrane of S aureus exposed to environment cues very different from those that B subtilis faces in its environment.